Impact of Criminal Acts on Point of Sales (POS) Business Operations in Karu Local Government Area of Nasarawa State - Obi, E. Nku (NIU Journal of Social Sciences, 2023)
This study examines Impact of criminal acts on Point of Sales (POS) Business Operations in Karu Local Government Area of Nasarawa State, Nigeria. Primary data were derived from questionnaires using twenty (20) businesses comprises of Medicine, Pharmaceuticals, Oil/Gas, Electronics, Electricals, Book Publishing, Bookshops, Agriculture, Agro-allied industry, Education, Telecommunication, Computer, Technology, Fashion design and Lifestyle, Event management, Entertainment, and Supermarket/Stores from the study area. The Technology Acceptance Model was adopted which states that an individual’s behavioral intention to adopt a system is determined by the perceived usefulness and perceived ease of use. However, it was revealed that the importance of Point of Sales (POS) business operations cannot be overlooked because of its electronic means of carrying out transactions, and as critical factor for a successful business, the necessary infrastructure such as internet access should be made available. It is imperative to strengthen and support Government’s strategy on financial inclusion compliance to rules and regulations on the management of agent banking so as to prevent financial and other predicate crimes that may be perpetrated by fraudsters due to the vulnerable nature of the business. Therefore, the paper recommends that competent authorities saddled with inspection responsibilities should ensure compliance on all guidelines and regulations by the CBN and other sector regulators on agent banking guidelines on adequate record keeping of transactions. Implore latest transaction monitoring systems for detecting transactions in line with international best practice and grant license to people of integrity to avoid abuse of the system, and CBN should ensure banks comply with their obligations to monitor agent’s activities. The operators should be routinely trained and identify red flags and indicators of POS machine. They should keep proper records of transactions on customers and the procedure for reporting suspicious activities of suspicious customers. Keywords: Criminal Acts, Financial Crime, Point of Sales (POS)